CAR T cells redirected to cell surface GRP78 display robust anti-acute myeloid leukemia activity and do not target hematopoietic progenitor cells - Hebbar, Nikhil; Epperly, Rebecca; Vaidya, Abishek; Thanekar, Unmesha; Moore, Sarah E.; Umeda, Masayuki; Ma, Jing; Patil, Sagar L.; Langfitt, Deanna; Huang, Sujuan; Cheng, Cheng; Klco, Jeffery M.; et al. (Nature communications, 2022)
Developing CAR T cells for acute myeloid leukemia (AML) has been hampered by a paucity of targets that are expressed on AML blasts and not on hematopoietic progenitor cells (HPCs). Here we demonstrate that GRP78 is expressed on the cell surface of primary AML blasts but not HPCs. To target GRP78, we generate T cell expressing a GRP78-specific peptide-based CAR, which show evidence of minimal fratricide post activation/transduction and antigen-dependent T cell differentiation. GRP78-CAR T cells recognize and kill GRP78-positive AML cells without toxicity to HPCs. In vivo, GRP78-CAR T cells have significant anti-AML activity. To prevent antigen-dependent T cell differentiation, we block CAR signaling and GRP78 cell surface expression post activation by using dasatinib during GRP78-CAR T cell manufacturing. This significantly improves their effector function in vitro and in vivo. Thus, targeting cell surface GRP78-positive AML with CAR T cells is feasible, and warrants further active exploration. There is an unmet need to discover suitable targets for CAR-T therapy in patients with acute myeloid leukemia (AML). Here the authors show that GRP78, a key regulator of the unfolded protein response, is highly expressed on the surface of primary AML blasts, but not on normal lymphocytes and hematopoietic progenitor cells, and that GRP78-CAR T have anti-AML activity in preclinical models.